PENINGKATAN PEMAHAMAN WARGA DESA SALBE MENGENAI KUALITAS AIR UMBUL PANOMBURAN MELALUI KEGIATAN PENYULUHAN KPPM INTEGRATIF - Hotnila Manurung; Francisko Simanjuntak; MHD. Tofik; Ruth Grace Purba; Ewin Handoco S (Abdi Jurnal Publikasi, 2025)
The earth's surface naturally not only holds water but water flows from upstream to downstream. Water quality is always influenced by the activities of living things. Water needs not only depend on quantity, but also on its quality. The purpose of this study was to determine the quality of water in the Panomburan spring and to conduct counseling/socialization through KPPM in Salbe village. Determination of water quality using 2 parameters, namely Physics and Chemistry. The physical parameters measured are temperature. The chemical parameters measured are pH, Dissolved Oxygen (DO) or Dissolved Oxygen. The method used in this activity is the observation method and counseling/socialization. The results of these parameters will be presented to the community in order to provide understanding for residents regarding water quality in the Panomburan spring. The results of the study that have been conducted in the Panomburan spring for the average value at all stations pH 6.915, DO 6.925, Temperature 20.375⁰C. it can be concluded that the Panomburan spring is classified as standard for the community. parameters that meet the quality standard requirements according to PP RI No. 22 of 2021, namely, Temperature, pH and DO. Keywords: Physics, Chemistry, Water Quality, Springs.